Does ESG Disclosure impact on the cost of debt? An analysis of Brazil and its regions - Iglesias, Thayla Machado Guimarães; Peixoto, Fernanda Maciel; Rogers, Pablo; Carvalho, Luciana (Revista de Administração da UFSM, 2025)
Purpose: This study investigates the relationship between Environmental, Social, and Governance (ESG) disclosure and the cost of debt for Brazilian companies. Additionally, it examines whether regional factors influence the ability to secure third-party financing. Design/methodology/approach: The analysis includes 576 firm-year observations from publicly traded, non-financial Brazilian companies listed on Bloomberg for the period 2016–2021. The data were structured using a dynamic System GMM panel (one- or two-step estimators). To assess the role of regionality, a static panel with random effects was employed to examine how Brazil's macroregions influence the cost of debt. Findings: ESG disclosure did not show a significant negative relationship with the cost of debt. Therefore, it cannot be inferred that creditors value ESG transparency or reward firms adopting such practices with lower borrowing costs. However, variations in the cost of debt were observed across Brazil's macroregions. Practical implications: Understanding the effects of ESG disclosure on corporate borrowing in Brazil supports the development of standards for non-financial reporting aimed at greater compliance and transparency in ESG initiatives. Enhanced disclosure can improve communication with investors and society, fostering trust and mitigating risks associated with investment decisions. Originality/value: This study advances ESG disclosure research by focusing on an emerging economy where ESG practices are not yet widely embraced. Moreover, it explores corporate financial behavior through the lens of debt costs, a relatively underexamined perspective in the existing literature.